Sausages: Nutrition, Safety, Processing and Quality Improvement - Carballo, Javier (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Sausages are privileged foods due to their diversity, nutritional value, deep roots in the culture of the peoples and economic importance. In order to increase the knowledge and to improve the quality and safety of these foods, an intense research activity was developed from the early decades of the past century. This book includes ten research works and a review showing important and interesting advances and new approaches in most of the research topics related to sausages. After an editorial of the Editor reflecting the aims and contents of the book, the initial five chapters deal with microbiological issues of the sausage manufacture (characterization and study of the bacterial communities of sausages, study of the metabolism and the technological and safety characteristics of concrete microbial strains, and use of starter cultures to improve the sausage quality). Chemical hazards also receive some attention in this book with a chapter on the optimization of the smoking process of traditional dry-cured meat products to minimize the presence of PAHs. The partial or total replacement of the traditional ingredients in sausages with unconventional raw materials for the obtaining of novel and varied products are the subject of three chapters. Next, a chapter is dedicated to another interesting topic, the search and the essay of natural substitutes for synthetic additives due to the increasing interest of consumers in healthier meat products. The book ends with an interesting review on the safety, quality and analytical authentication of halāl meat products, with particular emphasis on salami.